DNA Quality Assessment for Array CGH by Isothermal Whole Genome Amplification - Tineke E. Buffart; Marianne Tijssen; Thijs Krugers; Beatriz Carvalho; Serge J. Smeets; Ruud H. Brakenhoff; Heike Grabsch; Gerrit A. Meijer; Henry B. Sadowski; Bauke Ylstra (Cellular Oncology)
Background: Array Comparative Genomic Hybridization (array CGH) is increasingly applied on DNA obtained from formalin-fixed paraffin-embedded (FFPE) tissue, but in a proportion of cases this type of DNA is unsuitable. Due to the high experimental costs of array CGH and unreliable methods for DNA quality testing, better prediction methods are needed. The aim of this study was to accurately determine the quality of FFPE DNA input in order to predict quality of array CGH outcome. Material and Methods: DNA quality was assessed by isothermal amplification and compared to array CGH quality on 59 FFPE gastric cancer samples, one FFPE colorectal cancer sample, two FFPE normal uvula samples, one fresh frozen and six FFPE HNSCC samples. Gastric cancer DNA was also quality tested by β-globin PCR. Results: Accurate prediction of DNA quality using the isothermal amplification was observed in the colorectal carcinoma, HNSCC and uvula samples. In gastric cancer samples, the isothermal amplification was a more accurate method for selecting good quality DNA for array CGH compared to using PCR product lengths. The isothermal amplification product was used for array CGH and compared to the results achieved using non-amplified DNA in four of the samples. DNAs before and after amplification yielded the same segmentation patterns of chromosomal copy number changes for both the fresh DNA sample and the FFPE samples. Conclusion: The efficiency of isothermal DNA amplification is a reliable predictor for array CGH quality. The amplification product itself can be used for array CGH, even starting with FFPE derived DNA samples.